Autonomy in Forestry Training - Kishwan, Jagdish (Indian Forester, 1996)
The paper deals with the history and development of forestry research, training and education in India. An effort has heen made to highlight the pros and cons after the grant of autonomy to lCFRE and functioning of Indira Gandhi National Forest Academy and Directorate of Forest Education which are still under direct control of Govt. of India.lt has been suggested to bring them within the autonomous umbrella of Indian Council of Forestry Research and Education to allow them to develop. strengthen and flourish independent of Government control.